Hello! I have tried 10 times to do this problem and I am in need of assistance. I am looking to see if it is correct before i had the information in. Thank you
-3-4(t-5)=-2(t+3)+11
-3-4t+20=-2t+-6+11
17+-4t=-2t+5
12=2t 6=t
2 2
Hello! I have tried 10 times to do this problem and I am in need of assistance. I am looking to see if it is correct before i had the information in. Thank you
-3-4(t-5)=-2(t+3)+11
-3-4t+20=-2t+-6+11
17+-4t=-2t+5
12=2t 6=t
2 2
Hello.
Your work looks great to me. The beauty of this type of problem is your ability to check your answer of t=6.
-3 -4( [6] -5) = -2( [6] +3) +11
-3 -4(1) = -2(9) +11
-3 -4 = -18 +11
-7 = -7
Seems to check out to me. Always check your solutions when you can just plug them back into the initial problem.